Post-traumatic Growth Among Domestic Violence Survivors: A Systematic Review - Diah Rahayu; Hamidah Hamidah; Wiwin Hendriani (Universitas Ahmad Dahlan, 2019)
AbstractÂ Violence is an abusive behavior which includes any form of physical abuse, psychological abuse, sexual abuse, or neglect. Indonesia's National Commission on Violence against Women, reports that most violence is experienced by women. A majority of the violence occurs within the household domains, otherwise known as domestic violence. Both community and individual violence will result in the experience of trauma in its victims. Nevertheless, trauma caused by violence varies depending on the case and the proximity of the perpetrator to the victim. Many studies have attempted to explore the struggle experienced by victims of violence even although there are very little cases which specifically research cases of domestic violence. This review aims to examine how past empirical studies explain the struggles experienced by victims of violence, the strategy used in addressing their traumatic conditions, and the factors that contribute to a positive change. Posttraumatic Growth. Empirical studies in this review n = 25 which include sources from Psyche, Ebsco, Dissertation unpublish, etc. Indicates that there are several variables that contribute to the positive change process in individuals experiencing violent cases. Among them are social support, self-disclosure, and coping.Â Keywords: Posttraumatic growth, violence survivor, domestic violence.Â